Case control study of dry eye and related ocular surface abnormalities in Ibadan, Nigeria (2010)
Background: Tear instability is associated with symptoms of ocular discomfort and irritation. Many patients with dry eyes remain untreated due to improper diagnoses. Objective; To identify symptoms and surface abnormalities associated with dry eyes. Materials and methods: One hundred and fifty-six eyes of 78 subjects attending the Eye Clinic of the University College Hospital Ibadan were screened for dry eyes/tear instability using rose Bengal stain (graded 0-9), tear break-up time (TBUT), Schirmer's 1 tests, tear meniscus height and a standardised symptoms questionnaire. Grades 4-9 rose Bengal staining were considered as positive dry eye and were compared with grades 0-3 staining eyes as negative controls. Results: Mean tear meniscus height, Schirmer's test and TBUT were lower among cases than their corresponding control eyes. The difference between the mean Schirmer's test values of cases and their controls were statistically significant (P = 0.00 for right eyes and P = 0.002 for left eyes). Rose Bengal grades were inversely correlated with the mean Schirmer's values (Pearson correlation -0.429, P = 0.05 for right eyes and -0.335, P = 0.03 for left eyes) and TBUT (Pearson correlation -0.316, P = 0.05 for right eyes and -0.212, P = 0.06 for left eyes). About 95.8% of the cases were symptomatic, as opposed to 70.4% of the controls (P = 0.01, Fisher's exact test) and 95.8% of dry right eyes compared to 61.1 % of their controls had ocular surface abnormalities (P = 0.001), while 89.5% of dry left eyes compared to 62.7% of controls had surface abnormalities (P = 0.07). Conclusion: A close relationship exists between ocular irritation symptoms, surface abnormalities and functional evidence of tear instability. Such patients should be treated empirically or screened for dry eyes.